Multidimensional Seismic Control by Tuned Mass Damper with Poles and Torsional Pendulums - Haoxiang He; Wentao Wang; Honggang Xu (Shock and Vibration)
Due to the eccentric characteristics and the torsional excitation of multidimensional earthquakes, the dynamic response of asymmetry structure involves the translation-torsion coupling vibration and it is adverse to structural performance. Although the traditional tuned mass damper (TMD) is effective for decreasing the translational vibration when the structure is subjected to earthquake, its translation-torsion coupled damping capacity is still deficient. In order to simultaneously control the translational responses and the torsional angle of asymmetry structures, a new type of tuned mass damper with tuned mass blocks, orthogonal poles, and torsional pendulums (TMDPP) is proposed. The translation-torsion coupled vibration is tuned by the movement of the mass blocks and the torsional pendulums. According to the composition and the motion mechanism of the TMDPP, the dynamic equation for the total system considering eccentric torsion effect is established. The damping capacity of the TMDPP is verified by the time history analysis of an eccentric structure, and multidimensional earthquake excitations are considered. The damping effect of the traditional TMD and the TMDPP is compared, and the results show that the performance of TMDPP is superior to the traditional TMD. Moreover, the occasional amplitude amplification in TMD control does not appear in the TMDPP control. The main design parameters which affect the damping performance of TMDPP are analyzed.